PENGARUH PENAMBAHAN STARTER Pediococcus spp. PADA PEMBUATAN KECAP IKAN TERHADAP JUMLAH SENYAWA KIMIA DAN KOLONI BAKTERI - Wicaksana, Bima Risa Adil; Darmanto, Y S (Jurnal Pengolahan dan Bioteknologi Hasil Perikanan, 2013)
Trash fish were less widely used although they were quite highly potential. The commonly traditional processing smoking, salted boiled fish and fermentation. Fish processing by fermentation for example was fish sauce. One of the weaknesses of the fermentation process was the length of fermentation period. The acceleration of the fermentation process could be done by accelerating the hydrolysis process of fish protein, one of method is adding starter of lactic acid bacteria.The material used in this research was trash fish taken from TPI Tambakharjo, Semarang. Other materials used culture bacteria of Pediococcus halophilus CCRC 12576 and Pediococcus pentosaceus IFO 12230 taken from Study Centre Food and Nutrition of Gadjah Mada University, Yogyakarta.In this research there were two factors that is adding starter bacteria of Pediococcus spp and the period of fermentation. There were three treatments factor A consist of adding bacteria of P. halophilus 106, P. pentosaceus 106 and the combination (P. Halophilus + P. pentosaceus) 106 with salt addition 20% b/b. Factor B consist of tree treatment 10, 20 and 30 days and observed every ten days. Research using factorial experimental design3x3. The data was analyzed using analysis of variance (ANOVA) followed by HonestlySignificant Difference test(HSD).The results showed the addition of starter P. halophilus, P. pentosaceus and combition treatment with the long fermentation period of 30 days on the chemical parameters have significant effect on lowering the pH value, salt content reduction but have no significant effect on TVB increase and lowering of TPC but have significant effect on the increase LAB.The result of the final product sensory test of fish sauce in acceptance specification in the whole was liked.